2013
DOI: 10.1007/s12275-013-3492-z
|View full text |Cite
|
Sign up to set email alerts
|

Sunxiuqinia dokdonensis sp. nov., isolated from deep sub-seafloor sediment

Abstract: A novel facultatively anaerobic strain DH1(T) was isolated from deep sub-seafloor sediment at a depth of 900 m below the seafloor off Seo-do (the west part of Dokdo Island) in the East Sea of the Republic of Korea. The new strain was characterized using polyphasic approaches. The isolate was Gram-stain-negative, motile by gliding, non-spore-forming rods, oxidase-negative, and catalase-positive; and formed colonies of orange-red color. The NaCl range for growth was 0.5-7.0% (w/v) and no growth was observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…Facultative anaerobes have been isolated from a depth of 900mbsf in sediments of Sea-do located towards the western part of Dokdo Island in the East Sea of Republic of Korea (Chang et al, 2013). In addition, the present study also showed that there was no significant correlation between TVCa and TVCan indicating that the overlap between these two groups was less, possibly suggesting an existence of physiologically different communities.…”
Section: General Distribution Of Bacterial Abundance Down the Sedimencontrasting
confidence: 41%
“…Facultative anaerobes have been isolated from a depth of 900mbsf in sediments of Sea-do located towards the western part of Dokdo Island in the East Sea of Republic of Korea (Chang et al, 2013). In addition, the present study also showed that there was no significant correlation between TVCa and TVCan indicating that the overlap between these two groups was less, possibly suggesting an existence of physiologically different communities.…”
Section: General Distribution Of Bacterial Abundance Down the Sedimencontrasting
confidence: 41%
“…Among them, S. elliptica and S. rutile were isolated from shallow sea sediment in a sea cucumber farm and at Nagasuka Fishery Harbor, respectively. In contrast, S. dokdonensis and S. faeciviva were isolated from deep sub-seafloor sediment at a depth of 900 m below the seafloor off the west part of Dokdo Island and at a depth of 247.1 m below the seafloor off the Shimokita Peninsula, respectively [4] , [5] , [6] , [7] . Based on difference of sampling depth, these two groups were clearly separated through the phylogenetic tree ( Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 87%
“…Although several dilutions were performed, the 16S rRNA gene of Sunxiuqinia species was still detectable in the organic amended Desulfobulbus enrichments. The genus Sunxiuqinia is classified as a member of the Bacteroidetes , comprising heterotrophic, aerobic, or facultative aerobic species isolated from coastal marine sediments and deep sub-seafloor sediments ( Qu et al, 2011 ; Chang et al, 2013 ; Takai et al, 2013 ; Yoon and Kasai, 2014 ). Among the Desulfobulbaceae family, a co-culture has been reported of the host-associated Desulfobulbus oralis and Fusobacterium nucleatum .…”
Section: Discussionmentioning
confidence: 99%